Peran Kuliah Kerja Akuntansi (KKA) Dalam Meningkatkan Kompetensi Mahasiswa : Studi Pada Dinas PUPR dan Pegadaian Area Medan 2 - Nurul Azizah Hasibuan; Ayu Dwi Lestari; Saijuwita Sari; Novida Aprillya; Cayah Rahma Dani; Indra Fauzi (STARLA: Jurnal Pengabdian Masyarakat, 2026)
The Accounting Fieldwork Program (KKA) is a practice-based learning program designed to enhance students’ competencies through hands-on work experience at government agencies and companies. This study aims to analyze the role of KKA in improving students’ technical and non-technical skills. The method used is qualitative descriptive, employing observation, documentation, and direct participation techniques during the implementation of KKA at the North Sumatra Provincial Public Works and Spatial Planning Office and the Medan 2 Area Office of Pegadaian during the period of January–February 2026. The results indicate that students gained improved technical competencies in administrative and financial activities, such as document recording, report review, and data processing using applications. Additionally, students demonstrated enhanced soft skills, including communication, teamwork, discipline, and responsibility. Challenges encountered included initial adaptation difficulties and uneven task distribution; however, these were addressed through active communication and guidance from the host institutions. Overall, the Accounting Work-Study Program (KKA) makes a significant contribution to preparing students to enter the professional workforce through the enhancement of practical experience and the development of work ethic.